1979
DOI: 10.3109/00498257909042327
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of diclofenac sodium (Voltaren®) in animals and in man

Abstract: 1. The anti-inflammatory agent diclofenac sodium (o-[(2,6-dichlorophenyl)amino]phenylacetic acid sodium salt) is extensively metabolized by rat, dog, baboon and man. The main metabolites were isolated from the urine of all species and from the bile of rat and dog and identified by spectroscopy. 2. Metabolism involves direct conjugation of the unchanged drug, or oxidation of the aromatic rings usually followed by conjugation. Sites of oxidation are either position 3' or 4' of the dichlorophenyl ring or, alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 13 publications
5
75
0
Order By: Relevance
“…The hydroxylation of DF to 4OH-DF and 5OH-DF is catalyzed by CYP2C9 and CYP3A4, respectively (Tang, 2003). After glucuronidation, DF-AG can undergo further hydroxylation (Kumar et al, 2002), and hydroxylated DF-AG conjugates are major urinary metabolites (Stierlin et al, 1979).…”
Section: Diclofenac (Dfmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroxylation of DF to 4OH-DF and 5OH-DF is catalyzed by CYP2C9 and CYP3A4, respectively (Tang, 2003). After glucuronidation, DF-AG can undergo further hydroxylation (Kumar et al, 2002), and hydroxylated DF-AG conjugates are major urinary metabolites (Stierlin et al, 1979).…”
Section: Diclofenac (Dfmentioning
confidence: 99%
“…When given orally, absorption is rapid and complete (Stierlin et al, 1979;Peris-Ribera et al, 1991;Davies and Anderson, 1997). The metabolism of DF partitions between acyl glucuronidation and aryl hydroxylation (Tang, 2003), and the major metabolites are DF acyl glucuronide (DF-AG), 4Ј-hydroxy DF (4OH-DF), and 5-hydroxy DF (5OH-DF; Fig.…”
Section: Diclofenac (Dfmentioning
confidence: 99%
“…These observations have major implications for lead optimization for drugs metabolized by UGTs and for predicting human PK from preclinical data. b Clinical f m,UGT values were obtained from the literature as follows: ketoprofen, zidovudine, and gemfibrozil (Kilford et al, 2009); imipramine and furosemide (Soars et al, 2002); lorazepam (Greenblatt, 1981); levofloxacin (Fish and Chow, 1997); diclofenac (Stierlin et al, 1979); raloxifene and mycophenolic acid (Cubitt et al, 2009); and indomethacin (Duggan et al, 1972). …”
Section: Animal Scale-up Of Ugt Substratesmentioning
confidence: 99%
“…Metabolites of diclofenac were detected based on their MS and product ion spectra obtained by positive ion electrospray with data-dependent MS/MS. The identity of 4Ј-hydroxy-diclofenac (Stierlin et al, 1979) was confirmed by comparison with an authentic standard.…”
Section: Et Almentioning
confidence: 84%